Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/ncc.0000000000000888
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Interventions for Colorectal Cancer Survivors

Abstract: Background: Physical activity (PA) has been shown to improve total mortality and colorectal-specific mortality risk; however, colorectal cancer (CRC) survivors have lower rates of PA compared with survivors with other types of cancers. Objective: To examine the effect of PA interventions on CRC survivors. Methods: A systematic review and meta-analysis were conducted to identify randomized controlled trials that met the inclusion criteria, which included an intervention designed to increase PA and more than 1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 49 publications
(207 reference statements)
2
25
0
Order By: Relevance
“…Previous studies revealed that physical activity is a preventive factor and that regular physical activity may reduce frailty, particularly in older patients at a higher risk of disability 34,35 . A meta-analysis found that physical activity interventions significantly improved the disease-specific quality of life and physical activity levels among colorectal cancer survivors 36 . Therefore, it is crucial to develop an appropriate physical activity program for older cancer patients undergoing colorectal surgery to improve their functional status and prevent the occurrence of frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that physical activity is a preventive factor and that regular physical activity may reduce frailty, particularly in older patients at a higher risk of disability 34,35 . A meta-analysis found that physical activity interventions significantly improved the disease-specific quality of life and physical activity levels among colorectal cancer survivors 36 . Therefore, it is crucial to develop an appropriate physical activity program for older cancer patients undergoing colorectal surgery to improve their functional status and prevent the occurrence of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 A meta-analysis found that physical activity interventions significantly improved the disease-specific quality of life and physical activity levels among colorectal cancer survivors. 36 Therefore, it is crucial to develop an appropriate physical activity program for older cancer patients undergoing colorectal surgery to improve their functional status and prevent the occurrence of frailty.…”
Section: Predictors Of Frailtymentioning
confidence: 99%
“…Intervention: The intervention groups of included studies received the measures to change at least 1 lifestyle factor (BMI, diet, PA, smoking, and alcohol consumption). The lifestyle interventions can be changes to a single lifestyle factor, as well as mixed or comprehensive programs that promote lifestyle changes 19 . There was no limit to the frequency, duration, and intensity of interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the very visible nature of the experimental interventions targeting behavior change, it is generally difficult to blind participants. Therefore, we did not evaluate the blinding of participants in this review 19,23 . Studies were rated as having an overall “low risk of bias” when at least 50% of the remaining criteria were designated as low risk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation